Distracted While Reading? Changing to a Hard-to-Read Font Shields against the Effects of Environmental Noise and Speech on Text Memory - Halin, Niklas (Frontiers in Psychology, 2016)
The purpose of this study was to investigate the distractive effects of background speech, aircraft noise and road traffic noise on text memory and particularly to examine if displaying the texts in a hard-to-read font can shield against the detrimental effects of these types of background sounds. This issue was addressed in an experiment where 56 students read shorter texts about different classes of fictitious creatures (i.e., animals, fishes, birds, and dinosaurs) against a background of the aforementioned background sounds respectively and silence. For half of the participants the texts were displayed in an easy-to-read font (i.e., Times New Roman) and for the other half in a hard-to-read font (i.e., Haettenschweiler). The dependent measure was the proportion correct answers on the multiple-choice tests that followed each sound condition. Participants’ performance in the easy-to-read font condition was significantly impaired by all three background sound conditions compared to silence. In contrast, there were no effects of the three background sound conditions compared to silence in the hard-to-read font condition. These results suggest that an increase in task demand—by displaying the text in a hard-to-read font—shields against various types of distracting background sounds by promoting a more steadfast locus-of-attention and by reducing the processing of background sound.